Transient absorption spectroscopy of metal complexes : dithizonatophenylmercury(II) and derivatives - Bosman, Gurthwin Wendell (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.